Intervention of Collective Exercise on the Mental Health of Elderly Hypertensive Patients - Wenxin XU; Menglong LI; Jiwei YAO (Tehran University of Medical Sciences, 2016)
Background: Anxiety, depression, and other adverse psychological reactions are often observed in elderly hypertensive patients. Appropriate exercise is a safe form of adjuvant therapy without causing side effects among these patients, with consistent effects on patients' mental health. In this study, a collective exercise intervention experiment was conducted to evaluate the mental health of elderly hypertensive patients and to verify the effect of the psychological intervention of collective exercise. Method: A total of 115 elderly hypertensive patients aged 60-70 years old were selected as study subjects from May 2012 to January 2015 in Fuzhou City, Fujian Province, China. A total of 57 patients were included in the control group and 58 patients were assigned in the experimental group. Patients in the experimental group participated in a 12 weeks exercise intervention, while patients in the control group didn't participate in any regular physical exercise. Results: After intervention, the Symptom Checklist-90 (SCL-90), total score, somatization, obsessive-compulsive symptom, interpersonal sensitivity, depression, anxiety, hostility, and paranoia scores of the experimental group were significantly lower than those of the control group (P < 0.05). The positive coping style score of the experimental group was significantly higher than that of the control group (P<0.05); by contrast, the negative coping style score of the experimental group was significantly lower than that of the control group (P < 0.05). Conclusion: The mental health level and coping ability of elderly hypertensive patients can be effectively improved with the proposed treatment.